North Polar Tube Reduces the Risk of Epistaxis during Nasotracheal Intubation: A prospective, Randomized Clinical Trial - Ahmet Seli̇m Özkan; Sedat Akbas; Erol Toy; Mahmut Durmus (Elsevier, 2019)
ABSTRACT: Objective: In this study, a north polar tube (Portex® North Polar tube [Ivory PVC Portex tube; Smiths Medical International, Hythe, United Kingdom]) (NPT) and spiral tube (ST) were compared for their ability to provide a nasal airway in patients during maxillofacial surgery. Methods: Patients who were aged 18 to 65 years with American Society of Anaesthesiologists score 1 to 2 and Mallampati score 1 to 2 were included in the study. The anesthesia technique was standardized in all patients. Patients were divided into 2 groups randomly: the NPT (n = 35) and ST groups (n = 35). Anesthesia was administered with 1% to 2% sevoflurane and a mixture of 50% oxygen + 50% air in both groups. The mean arterial pressure and heart rate values of preinduction; preintubation; and the first, second, third, and fifth minutes of intubation were recorded. Epistaxis, intraoral bleeding, cuff burst, use of Magill pens, duration of intubation, intubation difficulty, laryngeal compression, head position change, and glottic grade were evaluated. Results: There were no significant differences between groups in terms of demographic data (gender, age, height, weight, body mass index, American Society of Anaesthesiologists score, and Mallampati score). Macintosh laryngoscopes were used during intubation in all patients. There was no significant difference between groups in terms of intubation difficulty, duration of intubation, use of Magill pens, and determination of the glottic grade (P > 0.05). Epistaxis was significantly lower in the NPT group than in the ST group (P = 0.012). Intraoral bleeding was significantly higher in the ST group than in the NPT group (P = 0.001). During intubation, laryngeal compression (Sellick maneuver) and head position changes were significantly lower in the NPT group than in the ST group (P = 0.003 and P < 0.001, respectively). There were no significant differences in mean arterial pressure and heart rate between the 2 groups. Conclusions: We conclude that the NPT was associated with less epistaxis and manipulations such as laryngeal compression and head position changes when compared with the ST during nasotracheal intubation. The velvet-soft polyvinyl chloride material of the NPT appears to be responsible for this advantage. Key words: Epistaxis, Nasotracheal intubation, North polar tube, Maxillofacial surgery, Spiral tube, Classification: sex, age, height, weight, body mass, index, American Society of Anaesthesiologists score, Mallampati score